Film Dokumenter sebagai Media Peningkatan Kualitas Pendidikan Karakter dan Literasi Budaya di Perguruan Tinggi - payuyasa, payuyasa; Ida Bagus Hari Kayana Putra; Gangga Lawranta; Ni Nyoman Ayu Suciartini (UHN IGB Sugriwa Denpasar, 2025)
The artistic journey in Bali has been ongoing for a long time. Various artistic activities taking place today are the result of a long journey of devotion by artists to art itself. One of the few art maestros now in his twilight years, with an extraordinary legacy, is I Ketut Muji. Based on initial research conducted by the author on maestro I Ketut Muji, there are many values and lessons that must be passed down to the artists in Bali. I Ketut Muji is a dance maestro with a strong character and style that, to this day, has not been inherited by anyone. The legacy of I Ketut Muji, as presented in this documentary film, is rich in educational and cultural literacy values, especially in preserving the traditional art of Balinese dance. The movements conveyed by the maestro in his dances embody educational philosophies that can serve as inspiration for pursuing education in its truest and most vibrant form. The primary goal of documenting the maestro's knowledge in film is to preserve and develop the values, ethics, and intellectual journey of I Ketut Muji for future generations, particularly for the artists in Bali. Featuring maestro I Ketut Muji in his twilight years in a documentary is of utmost importance. This film is produced to convey the knowledge, attitudes, and life perspectives of I Ketut Muji regarding dance and dancers to current and future Balinese dance practitioners. Therefore,